2008
DOI: 10.1097/tp.0b013e318169bf43
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Neoral C2 Monitoring in De Novo Cardiac Transplant Recipients Receiving Basiliximab Induction

Abstract: These results suggest that C2 monitoring is safe in de novo heart transplant patients. A low Neoral C2 range in combination with basiliximab induction resulted in preserved renal function without increased risk of acute rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Calcineurin inhibitors may interfere with ATG-induced apoptosis of activated lymphocytes, resulting in decreased efficacy; 36 consistent with this, heart transplant patients receiving an anti-CD25 (IL-2 receptor) Ab exposed to lower C2 levels had a lower rate of graft rejection. 9 Moreover, measurement of C2 levels or AUC may not be the optimal way of assessing the biological effect of CsA. Significant inter-patient variability in the degree of calcineurin inhibition produced by a consistent dose of CsA 37 has 'emphasised the importance of correlating biological measures of calcineurin inhibition with clinical outcome'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcineurin inhibitors may interfere with ATG-induced apoptosis of activated lymphocytes, resulting in decreased efficacy; 36 consistent with this, heart transplant patients receiving an anti-CD25 (IL-2 receptor) Ab exposed to lower C2 levels had a lower rate of graft rejection. 9 Moreover, measurement of C2 levels or AUC may not be the optimal way of assessing the biological effect of CsA. Significant inter-patient variability in the degree of calcineurin inhibition produced by a consistent dose of CsA 37 has 'emphasised the importance of correlating biological measures of calcineurin inhibition with clinical outcome'.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] In solid organ transplantation, the use of C0 monitoring has been associated with a high incidence of renal dysfunction. 8 In these patients, levels taken 2 h after a dose (C2) appear to correlate best with C max and area under the concentration-time curve 0-4 h (AUC 0À4h ), 9 and monitoring and dose adjustments based on C2 levels has been associated generally with improved renal function without an increased risk of graft rejection after heart, 10 liver 11 and renal transplantation, 12 although not all studies have demonstrated benefit with this approach. 13,14 Alterations in GI motility and mucosal integrity by conditioning regimens or GVHD mean that observations in solid organ transplantation may not apply to recipients of allo-SCT.…”
Section: Introductionmentioning
confidence: 99%
“…As cohort B patients were randomized into two reduced doses without a standard dose, we considered only cohort A. Patients randomized into ‘high’ C 2 range were the ‘standard‐CNI’ group, and those randomized into the ‘intermediate’ and ‘low’ C 2 range were included in the ‘low‐CNI’ group .…”
Section: Resultsmentioning
confidence: 99%
“…No kidney protection by CNI reduction was observed in several studies , whereas other studies found either a trend or better kidney protection, with the greatest benefit immediately after transplantation . In the study by Cantarovich et al ., the lower C 2 group was associated with a trend towards a lower incidence of acute rejection . Potena et al .…”
Section: Discussionmentioning
confidence: 99%
“…This scheme has been optimized and evolved to monitor a single sample at 2 H with the introduction of CsA microemulsion (Neoral R ) [8]. C2 monitoring has been shown to be predictive of outcomes in solid-organ transplants and compared with the conventionally measured trough level (C0), and has been shown to reflect the AUC and adequately estimate oral adsorption in transplant patients [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%